An effective monitoring framework and user interface design. (7th January 2014) - Chen, Tseng‐Yi; Yeh, Hsiu‐Lien; Wei, Hsin‐Wen; Sun, Mei‐ju; Hsu, Tsan‐sheng; Shih, Wei‐Kuan
Summary A distributed environment requires a monitoring system to oversee the operation of various distributed nodes. A monitoring service is crucial because it ensures a high‐quality computing environment and a reliable service. The interface and framework determine the effectiveness of a monitoring system. This paper uses the concept of user‐adaptive visualization to design its interface and proposes a flexible modular framework. Designers can use the proposed modular framework to flexibly extend existing modules, design visual interfaces to satisfy user requirements, and improve system failover schemes. The implementation of such a monitoring system for monitoring data preservation nodes is also provided. The system including fault‐tolerance and notification functions supports full monitoring services for Storage Resource Broker (SRB) or integrated Rule‐Oriented Data System (iRODS) based systems. The experimental results show that the proposed framework is suitable for data preservation services and is robust and responsive when faced with system failures. Copyright © 2014 John Wiley & Sons, Ltd.